Synergistic antitumor activity of artesunate and HDAC inhibitors through elevating heme synthesis via synergistic upregulation of ALAS1 expression - Cai-Ping Chen; Kun Chen; Zhiqi Feng; Xiaoan Wen; Hongbin Sun (Elsevier, 2019)
Artemisinin and its derivatives (ARTs) were reported to display heme-dependent antitumor activity. On the other hand, histone deacetylase inhibitors (HDACi) were known to be able to promote heme synthesis in erythroid cells. Nevertheless, the effect of HDACi on heme homeostasis in non-erythrocytes remains unknown. We envisioned that the combination of HDACi and artesunate (ARS) might have synergistic antitumor activity through modulating heme synthesis. In vitro studies revealed that combination of ARS and HDACi exerted synergistic tumor inhibition by inducing cell death. Moreover, this combination exhibited more effective antitumor activity than either ARS or HDACi monotherapy in xenograft models without apparent toxicity. Importantly, mechanistic studies revealed that HDACi coordinated with ARS to increase 5-aminolevulinate synthase (ALAS1) expression, and subsequent heme production, leading to enhanced cytotoxicity of ARS. Notably, knocking down ALAS1 significantly blunted the synergistic effect of ARS and HDACi on tumor inhibition, indicating a critical role of ALAS1 upregulation in mediating ARS cytotoxicity. Collectively, our study revealed the mechanism of synergistic antitumor action of ARS and HDACi. This finding indicates that modulation of heme synthesis pathway by the combination based on ARTs and other heme synthesis modulators represents a promising therapeutic approach to solid tumors. Keywords: Artesunate, HDAC inhibitor, Heme, ALAS1, Antitumor